Intervenção psicopedagógica na educação superior: acessibilidade aos estudantes com deficiência - Bortolazzo, Jéssica Colpo (2015)
This research aims to understand how to weave the teaching of relationships and learning of the subjects with disabilities in the context of higher education, seeking to identify psycho-pedagogical strategies and accessibility means that facilitate these processes. This study was conducted through a qualitative research, the research subjects were freshmen students at the Federal University of Santa Maria (RS), through the so-called B quota, for the disabled. The instruments of data collection were the field diary and semi-structured interview. The analysis method was used content analysis. The categories listed a priori were: School History previous Student Admissions in Higher Education, Accessibility and the Institutional System of UFSM, Classroom, Study Methods and The unknown Universe: Psychology. It was found that this study made it possible to bring out accessibility issues and educational psychology, realizing its implications in the learning process. In conclusion, learning processes and accessibility are essentially dynamic character. Higher education is going through paradigmatic changes, teaching methods and learning, programmatic and architectural structures, forms of communication, all these processes and their elements has been rediscussed in order to guarantee the permanence of studies and completion of all students who enter Higher Education.